the changing structure AND GROWTH OF EMPLOYMENT IN KERALA, 1993-94 to 2004-05 - S. Sumitha and Malathy Duraisamy (The Indian Journal of Labour Economics, 2009)
This paper examines the changes in the size, composition and growth of the workforce in Kerala during the years 1993-94 to 2004-05, using the aggregate National Sample Survey data. Comparable estimates are also presented for India. The average annual employment growth rate in Kerala is lower than that in India. The primary sector’s share in total employment has declined more sharply in Kerala than India. The secondary and tertiary sectors together accounted for 63.31 per cent of the workforce in Kerala in 2004-05 as compared to only 42.6 per cent in India. The available data also reveals a sharp growth in regular salaried employment and a reduction in the share of casual labour in Kerala and India during the given period. The employment elasticity of output is computed and the projections of employment growth are made for Kerala.